IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI PROGRAM THE SEVEN HABITS DALAM PEMBELAJARAN SEJARAH DI SMA PERADABAN BOARDING SCHOOL KOTA SERANG TAHUN 2025/2026 - Kamelia Putri; Agus Rustamana; Ana Nurhasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study aims to describe the implementation of character education through The Seven Habits program in history learning at SMA Peradaban Boarding School, Serang City, for the 2025/2026 academic year. This research is motivated by the importance of strengthening character education amidst increasingly complex developments, especially in the educational environment. History learning not only functions as a means of delivering academic material, but also has an important role in shaping the attitudes, morals, and character of students. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, in-depth interviews, documentation, and data triangulation. Research informants consisted of the principal, history teachers, and students. The results of the study indicate that the implementation of The Seven Habits program in history learning has been running well through the habituation of discipline, responsibility, cooperation, leadership, and critical thinking skills in students. This program is implemented both in the classroom learning process and in daily school activities. Supporting factors for program implementation include the boarding school-based and inclusive school environment, teacher support, and a positive school culture. Meanwhile, obstacles identified included differences in student character, varying levels of discipline, and the need for consistency in character building. Therefore, The Seven Habits program is considered to have a positive influence on character development in students learning history.